Nutrient Evaluation of an Enteral formula Compounded from Soya Bean (Glycine max), Finger Millet (Eleusine coracana), and Red Sorghum (Sorghum bicolor) - Elayeche Oko, Gregory; Akuirene, Joseph Odolomarun; Ofem Egom, Emmanuel (JURNAL BIOSAINS, 2026)
The high cost and limited availability of commercial enteral formulas in resource-poor settings like Nigeria necessitate the development of nutritious, affordable, and locally-sourced alternatives. Soybean, finger millet, and red sorghum are underutilized and locally available crops with exceptional nutritional profiles suitable for compounding enteral feeds for clinical nutrition. This study aimed to formulate and evaluate the nutrient composition of enteral feed powders compounded from blends of soybean, finger millet, and red sorghum. Mixed samples of soybean, finger millet, and red sorghum were purchased from the different markets in Cross River State. Nigeria and processed using various local methods (fermentation, roasting, and sprouting). The processed flours were combined in 30: 70 ratios to create distinct compounded formulations. The proximate composition (moisture, ash, crude protein, fat, dietary fibre, and carbohydrates) and mineral content (Mg, Fe, Ca, Zn, K, Mn, etc.) were determined using standard AOAC methods and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Data were analyzed using SPSS version 26. Results showed that soybean-based formulations were significantly higher in protein (28.68–34.82%), fat (16.64–23.58%), and dietary fibre (19.01–23.13%), while cereal-based formulations recorded higher carbohydrates (65.74–74.06%). Sprouting significantly enhanced the mineral density of the cereals, particularly calcium in finger millet (406.69 mg/100g) and iron in red sorghum (6.16 mg/100g). The final blended formulations (F1–F6) showed balanced profiles, with protein content ranging from 14.66% to 16.01% and enhanced mineral levels, especially in formulations containing sprouted ingredients. Blending soybean, finger millet, and red sorghum can produce nutritionally rich, cost-effective, and locally sustainable enteral feed powders. These formulations showed a viable alternative to imported commercial products, potentially improving nutrition support in Nigerian hospitals. Future research should focus on bioavailability, sensory evaluation, and shelf-life stability.